2013
DOI: 10.1097/mib.0b013e318281f31c
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus in Inflammatory Bowel Disease—Correlation with Different Therapeutic Regimens

Abstract: IBD is a risk factor for the presence of EBV DNA in blood, particularly in older patients and in those taking infliximab. C-reactive protein was not related to EBV DNA prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Because colon polyps are more common in elder people, the mean age of those in the control group was higher than that of the IBD group. It has been reported that EBV seroprevalence increased in the first 3 years and older age is a risk factor for EBV infection in colon mucosa [21]. We, therefore, believe that the higher EBV prevalence in IBD patients is due to the disease instead of age.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Because colon polyps are more common in elder people, the mean age of those in the control group was higher than that of the IBD group. It has been reported that EBV seroprevalence increased in the first 3 years and older age is a risk factor for EBV infection in colon mucosa [21]. We, therefore, believe that the higher EBV prevalence in IBD patients is due to the disease instead of age.…”
Section: Discussionmentioning
confidence: 65%
“…In our study, the risk of EBV infection increases at a rate of 3.7% per year. Similarly, age above 60 years was related to EBV DNA positivity in Magro's research [21]. Aging of the immune system, also termed as immunosenescence, may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…A further multiple regression analysis identified T-helper lymphocytopenia \250/lL as the best predictor for severe infections, with a positive predictive value of 0.53 and a negative predictive value of 0.97. In this respect, the risk of lymphoproliferative diseases related to immunosuppression is higher among patients who are seronegative for Epstein-Barr virus [155], and guidelines addressing organ and bone marrow transplantation recommend more aggressive monitoring in high-risk patients [156,157], although more research on this matter is warranted in IBD [158]. It should be emphasized that the immunization status of patients receiving immunomodulators should be considered regularly, and vaccination for varicella, human papilloma virus, influenza, hepatitis B, and pneumococcus, as well as routinely administered vaccines for tetanus, diphtheria, and poliomyelitis, might be prescribed [159].…”
Section: Routine Blood Monitoring Of Patients On Immunomodulator Therapymentioning
confidence: 97%
“…EBV positivity is an important infectious adverse event as it can lead to both malignant and non-malignant complications (223). EBV serology was positive in 98.3% of serological samples collected before IFX infusions in consecutive CD patients, showing latent viral presence (201).…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…Risk factors for detectable EBV DNA in whole blood include IBD, regardless of treatment, compared to healthy volunteers (p<0.05), IFX compared to non-biological treatments, age ≥60, and UC compared to CD (223). A 17 year-old IBD patient whose blood tested positive for EBV was treated with IFX without any reported adverse events (202).…”
Section: Epstein-barr Virusmentioning
confidence: 99%